Kesesuaian Penerapan Prinsip-prinsip Perjanjian Akad Mudharabah Perspektif Hukum Islam - Muhammad Rosyid (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2022)
This study determined to found the principles of the mudharabah muqayyadah contract agreement in the Islamic Financial Services Cooperative were following Islamic law or not? This study used a combined doctrinal (normative) and empirical (non-doctrinal) approach, interviews, observations and literature studies used to collect data. It was found that the values ??contained in the principles of the mudharabah contract agreement in the mudharabah financing product were in accordance with Islamic law based on (al-mabadi al-ammanah) a justice (al-Adalah), equality (al-Musawah), deliberation (al-Syura), mutual assistance (al-Ta'awun) and tolerance (at-Tasamuh). The factors that lead to breaking promises in mudharabah contracts were due to inadequate human resources, management of Islamic financial institutions, information systems and technology, and immorality in financing activities. The solution was to master the technical aspects, the philosophical law of Islamic economics and Islamic economic law. If there was a violation of the agreement, it would be resolved by a peace system (sulhu) then arbitration (tahkim) and by a judicial process (al-qadha).